2017
DOI: 10.26719/2017.23.5.375
|View full text |Cite
|
Sign up to set email alerts
|

Use of traditional medicine among type 2 diabetic Libyans

Abstract: The use of traditional medicines is common among patients with chronic illnesses and this practice might pose health risks. The use among Libyan patients with diabetes is unknown. Therefore, this study aimed to estimate the prevalence of traditional medicine use in the previous year among Libyans with type 2 diabetes and to examine the association between its use and sociodemographic and clinical characteristics of the patients. A cross-sectional study was conducted at a large diabetes centre in Tripoli. A sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…e CAM usage prevalence rates vary by country and region in patients with T2DM [43,44]. Our findings are comparable with studies conducted in Libya, Saudi Arabia, USA, Lebanon, and India, countries that also yielded low prevalence estimates (29%, 26%, 26%, 38%, and 30%, respectively) [44][45][46][47][48]. In contrast, the prevalence estimates of CAM use among T2DM patients were higher in Tanzania (78%), Sri Lanka (76%), and Malaysia (63%) [16,22,24].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…e CAM usage prevalence rates vary by country and region in patients with T2DM [43,44]. Our findings are comparable with studies conducted in Libya, Saudi Arabia, USA, Lebanon, and India, countries that also yielded low prevalence estimates (29%, 26%, 26%, 38%, and 30%, respectively) [44][45][46][47][48]. In contrast, the prevalence estimates of CAM use among T2DM patients were higher in Tanzania (78%), Sri Lanka (76%), and Malaysia (63%) [16,22,24].…”
Section: Discussionsupporting
confidence: 79%
“…It is important that friends and family are involved in diabetes education counseling regarding the efficacy and potential side effects of CAM use [22]. A small number of participants in the cohort included in this study use TM as referred by their healthcare professionals (6.06%), which corresponds with other reports [47,88]. Radwan et al [49] reported that only one in four patients inform their treating physician about the use of CAM, while Hernandez-Tejada et al [88]highlight a lack of communication with 8…”
Section: Discussionsupporting
confidence: 67%
“…Affordability of CAM was also established to motivate their use. [ 28 ] T2DM,[ 29 ] lower education,[ 24 ] and female gender[ 30 ] were established factors associated with CAM use. The findings from our investigation certainly confirm such an association in Saudi society.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Australia reported a prevalence of 8%, but the study gathered data from patients about their visits to CAM practitioners only and did not include data on CAM use in general by patients with diabetes [44]. Other studies reporting the lowest prevalence of CAM use included studies in Libya (29%), Saudi Arabia (26%), USA (26%), Israel (23%) and Jordan (17%) [15,26,29,43,52]. Pooled prevalence of CAM use was 51% (95%CI 43%, 59%).…”
Section: Prevalence Of Cam Usementioning
confidence: 99%